KEGIATAN SENAM UNTUK MENURUNKAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI DESA TUALANG KECAMATAN TUALANG - Ari Rahmat Aziz; Yunisman Roni; Nurhannifah Rizky Tampubolon; Masrina Munawarah Tampubolon; Ahmad Kautsar; Ardilla Nurliza; Aulia Oktavia (Gapenas Publisher, 2024)
This activity aims to examine the impact of the elderly gymnastics program on hypertension control in Tualang Village, Tualang District. This program involved 42 elderly participants and elderly posyandu cadres from 3 posyandu in the village. Activities carried out include exercising regularly, providing accurate information to support sports, and monitoring the impact of exercise on the health of the elderly. The results of the pre-test and post-test showed a decrease in blood pressure in the elderly who participated in gymnastics. In addition, the program also involves games and the preparation of mung bean porridge as a food component. The results of this activity revealed that the gymnastics program succeeded in increasing the knowledge and awareness of the elderly about the benefits of elderly gymnastics in handling hypertension. Exercise programs have an effect on lowering blood pressure in the elderly with hypertension. Overall, this program is considered a positive step in improving the quality of life of the elderly with hypertension in the region